2020
DOI: 10.3389/fphar.2020.00456
|View full text |Cite
|
Sign up to set email alerts
|

Cost-Effectiveness of Zoledronic Acid Versus Oral Alendronate for Postmenopausal Osteoporotic Women in China

Abstract: This study aims to estimate the cost-effectiveness of yearly intravenous zoledronic acid treatment versus weekly oral alendronate for postmenopausal osteoporotic women in China. Methods: We used a Markov microsimulation model to compare the cost-effectiveness of zoledronic acid with alendronate in Chinese postmenopausal osteoporotic women with no fracture history at various ages of therapy initiation from health care payer perspective.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 14 publications
(27 citation statements)
references
References 43 publications
0
26
0
1
Order By: Relevance
“…Women with creatinine clearances of less than 30–35 mL/min should not receive ZA or oral bisphosphonates. Cost-effective analyses show that denosumab is more cost-effective than oral bisphosphonates for treating osteoporosis [ 104 ], and ZA is more cost-effective than oral alendronate in Chinese women with osteoporosis [ 105 ].…”
Section: Oral and Intravenous Bisphosphonates And Rank Ligand Inhimentioning
confidence: 99%
“…Women with creatinine clearances of less than 30–35 mL/min should not receive ZA or oral bisphosphonates. Cost-effective analyses show that denosumab is more cost-effective than oral bisphosphonates for treating osteoporosis [ 104 ], and ZA is more cost-effective than oral alendronate in Chinese women with osteoporosis [ 105 ].…”
Section: Oral and Intravenous Bisphosphonates And Rank Ligand Inhimentioning
confidence: 99%
“…In our previous study ( You et al, 2020 ), in which we examined the cost-effectiveness of once-yearly injection of zoledronic acid compared with oral alendronate once a week for postmenopausal osteoporotic women without prior history of fracture in China, we concluded that zoledronic acid was cost-effective at all starting ages and even cost-saving in scenario analysis mainly based on zoledronic acid’s higher persistence leading to higher efficacy. In this study, we came to a similar conclusion that medication persistence plays a key role in shaping perceptions of fracture risk and osteoporosis drug effectiveness.…”
Section: Discussionmentioning
confidence: 99%
“…The development of this model adhered to the recommendations for the conduct of economic evaluations in osteoporosis ( Hiligsmann et al, 2019 ). We used an updated version of the previously validated individual-level state-transition model ( You et al, 2020 ) to estimate the impact of the compliance and persistence on the cost-effectiveness of alendronate treatment for Chinese postmenopausal osteoporotic women aged 65 and older. The model estimated the outcomes including the number of fracture quality-adjusted life-years (QALYs); direct societal costs in 2018 US dollars (USD); and incremental cost-effectiveness ratios (ICERs) per QALY gained.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations